Comparison fine spray nozzle for two phase flow within experimental and simulation - Ali, Hafiz Aizat (2015)
The conversion of bulk liquid into fine spray is very important nowadays in several industrial process and has many application in agriculture, meteorology, and medicine. So, the design to develop a fine spray nozzle was varies according to the application. However, new development in fine spray nozzle have been achieved and implement better than fine spray nozzle from Halton Group Asia Sdn. Bhd. Currently, the nozzle from Halton Group used are produce in bulk liquid condition. The improvement that make are the nozzle use low pressure with very fine water spray. This research was focused on comparison for fine spray nozzle between simulation and experimental. The observation focused on flow characteristic that produce by mist spray. Multiphase nozzle were used with air and water as a medium . Six pressure inlet different are used during the experiment. They are 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0 bar. They are three type of nozzles been tested Nozzle A, Nozzle B and Nozzle C. Nozzle A have eight air inlet slot which give a better performance compared to other nozzles. The result evaluated from this experiment are spray angle and the penetration. Nozzle A was sprayed with 3.0 bar of water and air pressure. Mass flowrate for this pressure are 5.67x10-3 kgs-1 for water and 2.698x10-4 kgs-1 for air. The angle of spray between experimental and simulation are 35.54° and 33.5° respectively. As a result, the percentage of similarity are 94.26%. High speed camera are used to visualize the result an the software were used to simulate the fine spray ANSYS FLUENT version 14.5. By using fine spray technology, it can trap dust and small particle in air inside kitchen hood more effective and can consume less water.